Nursing research : methods and critical appraisal for evidence-based practice - LoBiondo-Wood, Geri; Haber, Judith (St. Louis, Missouri : Elsevier, 2018)
This easy-to-understand textbook offers a comprehensive introduction to nursing research concepts and methods. Evidence-based practice is emphasised throughout, with clear guidelines for evaluating research and applying scientific evidence to practice. Coverage includes qualitative and quantitative research, appraising and critiquing research, critical thinking, and clinical decision-making using research information.
Integrating research, evidence-based practice, and quality improvement processes / Geri LoBiondo-Wood and Judith Haber -- Research questions, hypotheses, and clinical questions / Judith Haber -- Gathering and appraising the literature / Barbara Krainovich-Miller -- Theoretical frameworks for research / Melanie McEwen -- Introduction to qualitative research / Mark Toles and Julie Barroso -- Qualitative approaches to research / Mark Toles and Julie Barroso -- Appraising qualitative research / Dona Rinaldi Carpenter -- Introduction to quantitative research / Geri LoBiondo-Wood -- Experimental and quasi-experimental designs / Susan Sullivan-Bolyai and Carol Bova -- Nonexperimental designs / Geri LoBiondo-Wood and Judith Haber -- Systematic reviews and clinical practice guidelines / Geri LoBiondo-Wood -- Sampling / Judith Haber -- Legal and ethical issues / Judith Haber and Geri LoBiondo-Wood -- Data collection methods / Susan Sullivan-Bolyai and Carol Bova -- Reliability and validity / Geri LoBiondo-Wood and Judith Haber -- Data analysis : descriptive and inferential statistics / Susan Sullivan-Bolyai and Carol Bova -- Understanding research findings / Geri LoBiondo-Wood -- Appraising quantitative research / Deborah J. Jones -- Strategies and tools for developing an evidence-based practice / Carl A. Kirton -- Developing an evidence-based practice / Marita Titler -- Quality improvement / Maja Djukic and Mattia J. Gilmartin.
Includes bibliographical references and index.
Keywords: Nursing -- Research; Nursing Research -- methods; Research Design; Evidence-Based Nursing -- methods